Penggunaan Model Pembelajaran Collaborative Creativity Untuk Meningkatkan Kemampuan Berpikir Kreatif Siswa Pada Materi Pencemaran Lingkungan - Naufal Ahmad Muzakki; Fransisca Sudargo; Mimin Nurjhani (Magister Pendidikan Biologi, Universitas Negeri Medan, 2020)
The 2013 curriculum applies a scientific approach in the learning proses, therefore students are expected to have higher order thinking skills, one of which is creative thinking. Students' creative thinking skills can be trained by implementing student-centered learning. The purpose of this study was to analyze the using of collaborative creativity learning model on students' creative thinking abilities on the topic of environmental pollution. The method used in this study was a quasi-experiment with a pre-experimental research type and one group pretest-posttest research design. The subjects in this study was class X science 8 Senior High School in Bandung. Creative thinking abilities measured in this study include four aspects: fluency, flexibility, originality, and elaboration. Data of students' creative thinking skills were obtained from the pretest and posttest scores. Based on the results of data processing, the creative thinking ability of students has increased after using collaborative creativity learning model with a gain index value of 0.31 in the medium category. This shows that the use of collaborative creativity learning model can improve students' creative thinking ability on the topic of environmental pollution. The benefit of this research is that the Collaborative creativity learning model can be used as a reference for learning in class.